ITCH E3 ubiquitin ligase downregulation compromises hepatic degradation of branched-chain amino acids - Menghini, Rossella; Hoyles, Lesley; Cardellini, Marina; Casagrande, Viviana; Marino, Arianna; Gentileschi, Paolo; Davato, Francesca; Mavilio, Maria; Arisi, Ivan; Mauriello, Alessandro; Montanaro, Manuela; Scimeca, Manuel; et al. (Molecular metabolism, 2022)
OBJECTIVE: Metabolic syndrome, obesity, and steatosis are characterized by a range of dysregulations including defects in ubiquitin ligase tagging proteins for degradation. The identification of novel hepatic genes associated with fatty liver disease and metabolic dysregulation may be relevant to unravelling new mechanisms involved in liver disease progression METHODS: Through integrative analysis of liver transcriptomic and metabolomic obtained from obese subjects with steatosis, we identified itchy E ubiquitin protein ligase (ITCH) as a gene downregulated in human hepatic tissue in relation to steatosis grade. Wild-type or ITCH knockout mouse models of non-alcoholic fatty liver disease (NAFLD) and obesity-related hepatocellular carcinoma were analyzed to dissect the causal role of ITCH in steatosis RESULTS: We show that ITCH regulation of branched-chain amino acids (BCAAs) degradation enzymes is impaired in obese women with grade 3 compared with grade 0 steatosis, and that ITCH acts as a gatekeeper whose loss results in elevation of circulating BCAAs associated with hepatic steatosis. When ITCH expression was specifically restored in the liver of ITCH knockout mice, ACADSB mRNA and protein are restored, and BCAA levels are normalized both in liver and plasma CONCLUSIONS: Our data support a novel functional role for ITCH in the hepatic regulation of BCAA metabolism and suggest that targeting ITCH in a liver-specific manner might help delay the progression of metabolic hepatic diseases and insulin resistance.
Keywords: zvířata; Amino Acids, Branched-Chain; Obesity; lidé; ženské pohlaví; obezita; větvené aminokyseliny; nádory jater; Mice, Knockout; Female; down regulace; Liver Neoplasms; Down-Regulation; myši knockoutované; Non-alcoholic Fatty Liver Disease; Mice; myši; ubikvitinligasy; nealkoholová steatóza jater; Humans; Animals; Ubiquitin-Protein Ligases